Learning facilities, instructional activities and teacher assessments’ effects on students’ English achievement - Andreas Pehan Lebuan (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2017)
This study aims to analyze the effect of the learning facilities, instructional activities, and teacher assessments on students’ English achievement of SMPs/MTs in Ende. This research was ex-post facto, involving three independent variables and one dependent variable. This research was conducted at 10 SMP/MTs in Ende. The population of this study was eight graders of the schools i.e., 1146 students. The sample consisted of 278 students which established by using proportional random sampling technique. The research instruments were three questionnaires and tests. The data were analyzed by using partial correlations and multiple regressions. The result showed that r1(2,3) = -0.026, sig 0.670), r2(1,3) = -0.050, sig 0.41), r3(1,2) = 0.322, sig 0.000) and R1,2,3 = 0.425, sig 0.000.